Investigating the Role of Media in Shaping US Policy Towards the Palestinian Cause - GHERBI, Sonia; LAASEL, Mouchira (University of Eloued جامعة الوادي, 2024)
The relationship between media influence and U.S. foreign policy regarding the Palestinian cause is a subject of considerable scholarly interest and societal importance. This study investigates the role of media in shaping US policy towards the Palestinian cause. The study adopted a qualitative research approach based on a historical method in reviewing literature in the first chapter, in addition to descriptive and comparative methods to underscore the multifaceted role of media in shaping public opinion, setting agendas, and influencing policymakers while raising concerns about bias and misinformation concerning the Palestinian cause. The study reveals that media representation plays a significant role in influencing U.S. foreign policy toward the Palestinian cause, and indeed it made a substantial contribution in impacting policy-making in the USA. The study uncovers the predominant narratives in U.S. media. It identifies key factors that affect how media coverage shapes public opinion and political decisions and how Zionist lobbying controls and takes advantage of the U.S. alliance to serve its needs and accomplish its unethical actions. The study concluded that media significantly influences U.S. foreign policy and public opinion on the Israeli-Palestinian conflict. The media's coverage of the Israel-Palestine conflict is typically biased due to the outlet's editorial policies, national affiliations, and ideological leaning. Consequently, it is either pro-Israel or pro-Palestine, and perspectives are often reflected in the way the conflict is framed in coverage, which impacts the tone, sources used, visuals used, and overall plot playing a critical role in foreign policy decisions. تعد العلاقة بين تأثير الإعلام والسياسة الخارجية الأمريكية تجاه القضية الفلسطينية موضوعًا ذا اهتمام أكاديمي كبير وأهمية مجتمعية. تتناول هذه الدراسة دور الإعلام في تشكيل السياسة الأمريكية تجاه القضية الفلسطينية. اعتمدت الدراسة على منهجية بحثية نوعية، حيث استخدمت المنهج التاريخي في مراجعة الأدبيات في الفصل الأول، بالإضافة إلى المنهج الوصفي والمقارن لتسليط الضوء على الدور المتعدد الأبعاد للإعلام في تشكيل الرأي العام، وتحديد الأجندات، والتأثير على صانعي القرار، مع إثارة المخاوف بشأن التحيز والمعلومات المضللة المتعلقة بالقضية الفلسطينية. وتكشف الدراسة أن التمثيل الإعلامي يلعب دورًا هامًا في التأثير على السياسة الخارجية الأمريكية تجاه القضية الفلسطينية، وقد أسهم بشكل كبير في التأثير على صنع القرار السياسي في الولايات المتحدة. كما تستعرض الدراسة الأدبيات السائدة في وسائل الإعلام الأمريكية وتحدد العوامل الرئيسية التي تؤثر على كيفية تشكيل التغطية الإعلامية للرأي العام والقرارات السياسية، وكيف يستغل اللوبي الصهيوني التحالف الأمريكي لتحقيق مصالحه وأهدافه. خلصت الدراسة إلى أن للإعلام تأثيرًا كبيرًا على السياسة الخارجية الأمريكية والرأي العام بشأن الصراع الإسرائيلي-الفلسطيني، حيث تكون تغطية وسائل الإعلام لهذا الصراع عادةً منحازة بسبب السياسات التحريرية لوسائل الإعلام وانتماءاتها الوطنية وميولها الأيديولوجية. ونتيجة لذلك، تكون التغطية إما مؤيدة لإسرائيل أو مؤيدة لفلسطين، وغالبًا ما تنعكس هذه المواقف في طريقة تأطير الصراع، مما يؤثر على النبرة والمصادر المستخدمة والصور، ويؤدي دورًا حاسمًا في التأثير على القرارات السياسية الخارجية والرأي العام.
Literature and Civilization
Keywords: Israel; Media influence; Palestine; Public Opinion; U.S. Foreign Policy.; إسرائيل، تأثير الإعلام، فلسطين، الرأي العام، السياسة الخارجية الأمريكية.